Combating the rose tip-infesting sawfly: Ardis brunniventris HTG. - Cătălin Gutue; Florin Ungureanu (Agrarian Economy and Rural Development - Realities and Perspectives for Romania. 6th Edition of the International Symposium, November 2015, Bucharest, 2015)
For its great decorative value, the rose is present in parks and gardens as an ornamental plant isolated or in groups. Along with biotic factors, pests can affect the decorative value of these plants. Among them are Tenthredinidae wasps. The paper presents data on Ardis brunniventris attack frequency on rose plants from four landscape designs. It is also presented the negative impact of this pest on rose plants in suggestive images. Control measures are applied depending on the specific arrangements (public, private or with closed circuit). The urban environment influence the pest management. By applying preventive measures in association with the chemicals ensures a good protection against this pest.
Keywords: 330; rose; pests; wasp; control